Decoding ‘I Do’s and ‘I Don’ts’: Exploring the Surge in Indian Divorce Rates - Charu (Recent Trends in Social Studies, 2024)
The research explores the evolving dynamics of marriage and divorce in India, highlighting the rise in divorce rates due to increased stress, lack of bonds, and female independence. The study argues that women's financial self-sufficiency has led to a decrease in their willingness to tolerate unsatisfactory or abusive marriages. The research also emphasizes the influence of urbanization, Westernization, and changing attitudes toward marriage as factors contributing to the increase in divorce rates. The study underscores the need for societal changes that support women's financial independence and their right to choose their marital paths, free from societal pressure and financial dependence. The research also highlights the importance of addressing the root causes of unsatisfactory marriages, such as societal expectations and gender roles, to create a more equitable and fulfilling marital landscape for all individuals. The study emphasizes the urgent need for societal reforms that bolster women's financial independence and uphold their right to choose marital paths devoid of societal pressure and financial constraints. Additionally, it underscores the importance of confronting root causes of marital dissatisfaction, such as entrenched societal expectations and rigid gender roles, to cultivate an equitable and fulfilling marital landscape for all individuals. Furthermore, it investigates how education and exposure influence perceptions of marriage and divorce, especially among younger cohorts. It advocates for increased understanding and tolerance of varied marital paths to create an inclusive and nurturing atmosphere where people can seek fulfilling relationships according to their preferences. Additionally, it suggests implementing tailored support programs to equip couples with the tools and assistance needed to overcome obstacles and cultivate strong partnerships. Ultimately, the study envisions a future where marriages prioritize mutual respect, parity, and individual satisfaction over societal expectations or financial imperatives.
Keywords: Divorce; Individualism; Marriage; Traditional Norms and Westernization